PUBLIC SECTOR ACCRUAL ACCOUNTING ADOPTION: EVALUATING GLOBAL REFORM PROGRESS AND IMPLEMENTATION BARRIERS - Yuyun Yuniarti Layn; Nirwana Nirwana; Aini Indirajawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to evaluate global developments in the adoption of accrual-based accounting in the public sector and identify various implementation barriers faced by governments in various countries. Accrual accounting is seen as a crucial reform in public financial management because it can improve transparency, accountability, and the quality of financial information for decision-making. However, the level of adoption and success of its implementation show significant variations across countries and regions. This study uses a literature review method by examining reputable international journal articles, international organization reports, and policy publications relevant to public sector accounting reform. The results show that despite significant progress in the formal adoption of accrual accounting, substantive implementation still faces various challenges, such as limited human resource capacity, the technical complexity of accounting standards, organizational resistance and bureaucratic culture, limitations in information systems, and weak political and institutional support. Furthermore, differences in social, economic, and governance contexts also influence the effectiveness of this reform. This study concludes that the success of accrual accounting adoption in the public sector is determined not only by formal regulations, but also by institutional readiness, stakeholder commitment, and a sustainable implementation strategy. These findings are expected to provide conceptual contributions to the development of public sector accounting literature and serve as a reference for policymakers in designing more effective public finance reforms.